National standard system on circular economy in Vietnam and proposal for some policies - Doan Thi Thanh Van; Nguyen Kieu Lan Phuong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Circular economy (CE) is a new concept mentioned first in Vietnam’s revised Law on Environmental Protection 2020. Although its activities have been regulated in many national development strategies and policies, but there is still no national standard framework for the circular economy in Vietnam. Therefore, the development of a national standard system on CE at this time is one of the important efforts to establish a national standard framework for Vietnam in the coming years. The objective of the current study is to propose a system of standards to serve the circular economy in Vietnam, thereby to propose a list of policies to be implemented in specific fields. To achieve the above goal, the authors have reviewed the literature, standardization activities in the knowledge economy in Vietnam, international experiences in the development and application of standards relevant to CE business model, and studied the requirements for standardization activities for the development of the CE in Vietnam. As a result, we have drafted a list of 65 standards that need to be developed and its roadmap for implementation. This list will guide standardization activities in the coming time to serve the development of the CE in Vietnam. However, this list only provides the most general and necessary standards to create a framework, guidelines, and supporting tools organizations. Depending on the practical needs of each industry or field, it is necessary to study and build a list of more complete and detailed standards to best serve that industry or field. Code: 23013101